Decorative high-quality gravel concrete and construction method thereof
Through scientific proportioning and optimization of construction technology, high-quality concrete for sand and gravel decorative properties has been solved, and the construction of traditional exposed stone decorative concrete has been completed and poor environmental protection is achieved, and efficient and environmentally friendly sand and gravel display effect and high durability are achieved. Reduced maintenance costs.
Patent Information
- Application Number
- CN202411505674.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional exposed stone decorative concrete is time-consuming and has poor environmental protection. It is prone to dust accumulation on the surface and is difficult to clean. It has low strength and poor durability. It requires additional protective coating.
The high-quality concrete with sand and gravel decorative properties is used, and through scientific proportioning, the use of reinforcement, defoaming powder and water reducing agent, combined with the optimized construction technology, a natural transitional sand and gravel structure is formed, which reduces secondary surface treatment, improves construction efficiency and Environmental protection.
It realizes the appearance of the sand and gravel profile without additional sandblasting or pickling treatment, saves construction time and cost, improves environmental protection and decorative effect, is easy to clean, and the concrete structure is dense, has high compressive strength and durability, reducing Reliance on transparent protective coatings.
Smart Images

Figure CN119430757A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of municipal and building materials, in particular to high-quality decorative concrete with sandstone properties and a construction method thereof. Background Art
[0002] At present, the surface colors of decorative concrete are divided into primary colors and colored colors, and the surface organizational structures include texture finishes, exposed stone finishes, and mechanical finishes. Decorative concrete can also achieve simulated stone decorative effects. In addition, decorative concrete has also made significant progress in construction technology and application scenarios. Through the improvement of modern technology, concrete can not only achieve a variety of color options by adding different pigments and admixtures, but also achieve a variety of decorative effects by adjusting the surface structure. For example, by controlling the degree of exposure of concrete aggregates, fine texture finishes and exposed stone finishes can be created; while mechanical finishes are processed by mechanical equipment to form a smooth or special textured surface, making it more modern in appearance and texture.
[0003] However, in the construction of traditional exposed stone facing concrete, revealing the sandstone structure often requires cumbersome processes such as sandblasting, acid washing or sand pad technology. Such methods not only require a lot of manual operations, but also require multiple surface treatments, such as grinding, sandblasting, cleaning and other steps, which not only increase the construction time, but also generate a lot of dust or acid, affecting the environmental friendliness of the construction environment. Due to the need for additional operations, the entire process is time-consuming and costly, and errors are prone to occur during the construction process, affecting the final decorative effect;
[0004] Secondly, the surface of traditional exposed stone concrete is easy to accumulate dust and difficult to clean: due to the uneven surface treatment of traditional exposed stone concrete, the exposure depth of the stone varies, forming an uneven surface structure, which is easy to accumulate dust, stains and water stains during use, especially in the inner corners. This surface structure is difficult to keep clean. In outdoor environments, daily cleaning work requires a lot of manpower and time, and the cleaning effect is not good. Due to the complexity of surface maintenance, it is difficult for traditional exposed stone concrete to maintain its original appearance during use, and long-term exposure will lead to a decline in decorative effect;
[0005] Finally, traditional concrete has low strength and poor durability, and needs to be coated with protective coatings later: Although the existing exposed stone concrete can form a certain sand and gravel structure in terms of surface decorative effect, due to the lack of the use of reinforcing agents and other modifying materials, the structure of the concrete is relatively loose after surface treatment, and the density is poor, resulting in its low bonding strength. In order to avoid wear and weathering of the concrete surface, traditional processes often require the application of transparent protective coatings on the concrete surface, which increases the complexity and cost of subsequent maintenance. Moreover, even if coatings are used for protection, due to the poor durability of the concrete itself, it is prone to cracks and falling off after long-term use, affecting the service life and economic benefits of application scenarios such as sidewalks. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides high-quality concrete with sand and gravel decoration properties and a construction method thereof, which solves the problems that traditional construction methods are time-consuming and lack environmental friendliness.
[0007] To achieve the above objectives, the present invention is implemented through the following technical scheme: high-quality concrete with sand and gravel decoration, including the following components: 400 to 500 parts of cement, 20 to 25 parts of reinforcing agent, 0.4 to 0.5 parts of defoaming powder, 12 to 16 parts of water, 115 to 147 parts of water, 117 to 147 parts of extra fine sand, 591 to 739 parts of medium fine sand, 443 to 560 parts of coarse sand, 443 to 560 parts of gravel, and 0.3 to 0.5 parts of admixture.
[0008] Preferably, the water reducer is a polycarboxylic acid-based water reducer, which is specifically copolymerized from polyether monomers, acrylic acid, ammonium persulfate, thioglycolic acid, maleic anhydride, phosphate ester, and the like.
[0009] Preferably, the admixture is a shrinkage reducing agent, which is specifically composed of polypropylene glycol, ethylene oxide methanol additives, ethylene oxide propylene oxide block polymers, ethylene oxide propylene oxide random polymers, ethylene oxide cycloalkyl additives, ethylene oxide methyl additives, ethylene oxide phenyl additives, ethylene oxide propylene oxide block polymer methylphenyl additives, ethylene oxide methanol added at both ends, and ethylene oxide dimethylamino additives.
[0010] Preferably, the diameter of the medium-fine sand ranges from 0.3 mm to 0.8 mm, the diameter of the extra-fine sand ranges from 0.075 mm to 0.3 mm, the diameter of the coarse sand ranges from 0.8 mm to 5.1 mm, and the diameter of the gravel ranges from 3 mm to 10 mm.
[0011] The construction method of high-quality concrete with sandstone decoration includes the following steps:
[0012] S1. Material preparation: During the material preparation stage, the following materials must be accurately weighed in proportion: cement, reinforcing agent, defoaming powder, water reducing agent, water, sand, gravel and admixtures. After all materials are prepared, they should be placed in the designated area in order to ensure that the proportions are correct before construction.
[0013] S2. Mixing cement slurry: First, corresponding amounts of cement and reinforcing agent are mixed as predetermined, and added into a mixer at a suitable temperature, then defoaming powder and admixture are added, and finally, water and water reducing agent are premixed to obtain a composite solution A, and then the composite solution A is slowly poured into the mixer and stirred to obtain a uniform cement slurry with no segregation and good fluidity;
[0014] S3, mixing cement mortar: after the mixing in step S2 is completed, the temperature of the mixer is maintained, and then ultra-fine sand is first added and then medium-fine sand is added to make cement mortar;
[0015] S4, mixing to concrete: maintaining the mixer speed in step S3, adding coarse sand and gravel to the cement mortar and mixing to form slightly unsaturated concrete;
[0016] S5. Concrete pouring: Pour the mixed concrete evenly into the mold, use high-frequency vibrating equipment to compact the concrete, and quickly level it after compaction to ensure that the concrete surface is aligned with the predetermined elevation;
[0017] S6. Curing concrete: After pouring the concrete, cover it with wet cotton cloth for moisturizing. The wet cotton cloth needs to be covered overhead, and then covered with a layer of plastic film to keep it airtight and the wet cotton cloth moist. Curing takes 7 to 14 days.
[0018] Preferably, in the step S2, the mixed water and water reducing agent are added to a mixer, the speed of stirring is 30 r / min to 50 r / min, and the stirring time is 3 min to 5 min.
[0019] Preferably, in the step S3, when adding the extra-fine sand and the medium-fine sand, the rotation speed of the mixer is 40 r / min to 60 r / min, and the stirring time is 5 min to 8 min.
[0020] Preferably, in the step S5, the vibration frequency of the high-frequency vibration equipment is 3000 times / min to 5000 times / min, and each position needs to be vibrated for 5S to 10S.
[0021] Preferably, in the step S6, the wet cotton cloth must not directly contact the concrete surface and must be replenished with water in time to keep it moist, and the curing temperature must be maintained above 8°C.
[0022] The present invention provides high-quality concrete with sandstone decoration and a construction method thereof, which has the following beneficial effects:
[0023] 1. The present invention achieves excellent decorative effect by naturally revealing the outline of sand and gravel after pouring concrete to form a patterned organizational structure, without the need for additional secondary surface treatment operations such as sandblasting or pickling, thereby saving construction time and labor costs, improving construction efficiency, and reducing environmentally unfriendly factors such as dust, making the construction process more efficient and environmentally friendly.
[0024] 2. The present invention forms a naturally transitioned sand and gravel structure through reasonable material ratios and optimized construction technology. The surface has no obvious edges and corners and is easy to clean. During use, dust and stains are not easy to accumulate and can maintain their original appearance for a long time. Frequent cleaning and maintenance are not required, and maintenance costs are greatly reduced. It is suitable for long-term use in outdoor environments.
[0025] 3. The present invention makes the concrete structure more compact, has higher compressive strength and durability, and has no bubbles or cracks on the surface through the scientific ratio of the reinforcing agent, defoaming powder and water reducing agent. The shrinkage reducing agent can achieve the purpose of improving the quality of concrete and extending the service life through the different chemical components. At the same time, due to the dense structure, no additional transparent protective coating is required during use. The cast-in-place concrete has good integrity with the base layer, which can significantly improve the compression resistance and wear resistance of the sidewalk pavement, extend its service life, and give the sidewalk better durability and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The figure is a flow chart of the method steps of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Embodiment 1:
[0029] Please see attached Figure 1 The embodiment of the present invention provides a high-quality concrete with sandstone decoration, including the following components: 400 to 500 parts of cement, 20 to 25 parts of reinforcing agent, 0.4 to 0.5 parts of defoaming powder, 12 to 16 parts of water reducing agent, 115 to 147 parts of water, 117 to 147 parts of extra-fine sand, 591 to 739 parts of medium-fine sand, 443 to 560 parts of coarse sand, 443 to 560 parts of gravel, and 0.3 to 0.5 parts of admixture;
[0030] The water reducer adopts a polycarboxylic acid water reducer, which is specifically copolymerized by polyether monomer, acrylic acid, ammonium persulfate, thioglycolic acid, maleic anhydride, phosphate ester, etc.;
[0031] The admixture is a shrinkage reducing agent, which is specifically composed of polypropylene glycol, ethylene oxide methanol additives, ethylene oxide propylene oxide block polymers, ethylene oxide propylene oxide random polymers, ethylene oxide cycloalkyl additives, ethylene oxide methyl additives, ethylene oxide phenyl additives, ethylene oxide propylene oxide block polymer methyl phenyl additives, ethylene oxide methanol added at both ends, and ethylene oxide dimethylamine additives;
[0032] The diameter of medium-fine sand ranges from 0.3mm to 0.8mm, the diameter of extra-fine sand ranges from 0.075mm to 0.3mm, the diameter of coarse sand ranges from 0.8mm to 5.1mm, and the diameter of gravel ranges from 3mm to 10mm;
[0033] The construction method of high-quality concrete with sandstone decoration includes the following steps:
[0034] S1. Material preparation: During the material preparation stage, the following materials must be accurately weighed in proportion: cement, reinforcing agent, defoaming powder, water reducing agent, water, sand, gravel and admixtures. After all materials are prepared, they should be placed in the designated area in order to ensure that the proportions are correct before construction.
[0035] S2. Mixing cement slurry: First, corresponding amounts of cement and reinforcing agent are mixed as predetermined, and added into a mixer at a suitable temperature, then defoaming powder and admixture are added, and finally, water and water reducing agent are premixed to obtain a composite solution A, and then the composite solution A is slowly poured into the mixer and stirred to obtain a uniform cement slurry with no segregation and good fluidity;
[0036] S3, mixing cement mortar: after the mixing in step S2 is completed, the temperature of the mixer is maintained, and then ultra-fine sand is first added and then medium-fine sand is added to make cement mortar;
[0037] S4, mixing to concrete: maintaining the mixer speed in step S3, adding coarse sand and gravel to the cement mortar and mixing to form slightly unsaturated concrete;
[0038] S5. Concrete pouring: Pour the mixed concrete evenly into the mold, use high-frequency vibrating equipment to compact the concrete, and quickly level it after compaction to ensure that the concrete surface is aligned with the predetermined elevation;
[0039] S6. Curing concrete: After pouring the concrete, cover it with wet cotton cloth for moisturizing. The wet cotton cloth needs to be covered overhead, and then covered with a layer of plastic film to keep it airtight and the wet cotton cloth moist. Curing for 7 to 14 days;
[0040] In step S2, the mixed water and water reducing agent are added to the mixer, and the speed of stirring is 30r / min~50r / min, and the stirring time is 3min~5min; in step S3, when adding extra fine sand and fine sand, the speed of the mixer is 40r / min~60r / min, and the stirring time is 5min~8min; in step S5, the vibration frequency of the high-frequency vibration equipment is 3000 times / min~5000 times / min, and each position needs to be vibrated for 5S~10S; in step S6, the wet cotton cloth must not directly contact the concrete surface and must be replenished with water in time to keep it moist, and the curing temperature must be maintained above 8°C.
[0041] Summary: This embodiment is based on the technical solution of the present invention, adopts scientific and reasonable material ratios and construction steps, and the combined use of reinforcing agent, defoaming powder and water reducing agent significantly improves the fluidity, uniformity and durability of concrete. The optimization of vibration frequency and time ensures a smooth surface without bubbles. The overall operation is simple, the curing period is short, and the construction efficiency is high.
[0042] Example 2 (Comparative Example): Direct-cast exposed stone concrete
[0043] Specific steps:
[0044] Material preparation: Weigh 450 parts of cement, 180 parts of sand, and 850 parts of gravel. No reinforcing agent, defoaming powder or admixture is used. The materials are arranged neatly.
[0045] Mixing cement mortar: Mix cement and water directly without using any reinforcing agent, and stir evenly to obtain cement slurry.
[0046] Mixing concrete: Add sand and gravel in proportion and mix for 5 minutes without considering the particle size of sand.
[0047] Pouring concrete: Use the direct pouring method, pour the concrete directly into the formwork, and vibrate it with a device with a vibration frequency of 1500Hz.
[0048] Surface treatment: After the concrete hardens, sandblasting is used to expose the stones to achieve an exposed stone effect.
[0049] Curing concrete: Apply transparent protective coating on the concrete surface and cure for 14 days.
[0050] Summarize:
[0051] This embodiment adopts the traditional positive construction process. Although the materials are simple and easy to obtain, the strength and uniformity of the concrete are not as good as the optimized formula because no reinforcing agent and defoaming powder are added. The sandblasting process is relatively complicated and consumes a lot of manpower and time. The overall construction time is long and the surface treatment process is cumbersome.
[0052] Example 3 (Comparative Example): Exposed Stone Concrete with Back-beating Method
[0053] Specific steps:
[0054] Material preparation: 420 parts of cement, 150 parts of sand, 900 parts of gravel, some reinforcing agent was added, but no defoaming powder and water reducing agent were used.
[0055] Mixing cement mortar: The enhancer is mixed directly with cement, the mixing is uneven, and the ratio is not optimized.
[0056] Mix concrete: Add coarse sand and fine sand in a ratio of 4:1, add gravel directly, and stir for 5 minutes.
[0057] Pouring concrete: Use the reverse method, first lay the gravel, then pour, and use a lower frequency vibrating device to process the concrete.
[0058] Surface treatment: After the concrete hardens, the surface is treated by acid erosion to expose the stones.
[0059] Curing concrete: After pickling, carry out surface cleaning and 7 days of moisturizing curing.
[0060] Summarize:
[0061] This embodiment uses the reverse method, and the acid washing process exposes the stones, but due to the acid treatment, the concrete surface is prone to uneven depth. Although the reinforcing agent partially improves the material performance, due to the lack of defoaming powder and water reducing agent, the overall fluidity and uniformity of the concrete are poor, the construction process is time-consuming and the subsequent treatment is complicated.
[0062] Example 4 (Comparative Example): Sand Pad Finishing Concrete
[0063] Specific steps:
[0064] Material preparation: 400 parts of cement, 200 parts of sand, 950 parts of gravel, no admixtures or defoaming powder used.
[0065] Mixing cement mortar: directly mix cement and sand without using any reinforcing agent and simply stir.
[0066] Mix concrete: Add coarse sand and gravel in proportion and mix for 5 minutes.
[0067] Pouring concrete: Use the sand pad process, place the sand pad on the concrete surface and smooth it out.
[0068] Curing concrete: The curing process is 7 days with simple covering with wet cloth.
[0069] Summarize:
[0070] This embodiment adopts a more traditional sand pad process with simple materials and a relatively simple construction process. However, since no admixtures and defoaming powder are added, the overall fluidity and durability of the concrete are not as expected, the finishing effect is difficult to ensure uniformity, and the surface needs to be repeatedly smoothed during construction, affecting construction efficiency.
[0071] Example 5 (Comparative Example): Acid-etched facing concrete
[0072] Specific steps:
[0073] Material preparation: 450 parts of cement, 150 parts of sand, 850 parts of gravel, no reinforcing agent and defoaming powder are added.
[0074] Mixing cement mortar: After mixing cement with water, mix cement slurry directly without using reinforcing agents.
[0075] Mixing concrete: Use coarse sand and fine sand in a ratio of 3:1. The gravel is of rough quality, and there are many pores inside the concrete after mixing.
[0076] Pouring concrete: Use the acid erosion method to treat the finish. The exposed depth of the stones varies, and the surface needs to be cleaned after acid washing.
[0077] Curing concrete: Curing for 7 days after pickling, without using plastic film for sealing and protection during the process.
[0078] Summarize:
[0079] This embodiment uses the acid erosion method. Although it can form an exposed stone effect, the acid treatment makes the surface uneven, there are many bubbles inside the concrete, and additional treatment is required after acid cleaning. There is a lack of closed protection during the curing process, which easily causes surface pollution.
[0080] Summary:
[0081] Embodiment 1 (technical solution of the present invention): The process is simple, the material ratio is scientific and reasonable, the reinforcing agent, defoaming powder and admixture are used, the construction efficiency is high, the finishing effect is flat and smooth, the environmental protection is strong, the curing period is short, and the comprehensive performance is excellent;
[0082] Example 2 (comparative example, exposed stone concrete with positive method): Although the traditional construction process is adopted, the performance of the concrete is poor due to the lack of reinforcing agent and defoaming powder, and the sandblasting process is time-consuming and labor-intensive, and the construction is complicated;
[0083] Example 3 (comparative example, reverse-beating exposed stone concrete): the acid washing process was used, the stone exposure effect was unstable, the surface treatment was relatively complicated, the overall fluidity and uniformity of the concrete were poor, and it took a long time;
[0084] Example 4 (Comparative Example, Sand Pad Process Finished Concrete): Although the sand pad process is relatively simple, the finishing effect is difficult to guarantee, the fluidity and durability of the concrete are poor, and frequent leveling is required, resulting in low construction efficiency;
[0085] Example 5 (comparative example, acid-etching finishing concrete): The stone exposure effect of the acid-etching method is uneven, the acid treatment has a great impact on the concrete surface, the curing process is complicated and environmentally friendly, and it is easy to leave pollution after construction;
[0086] By comparison, it can be seen that the technical solution of the present invention is significantly superior to the traditional process in terms of material selection, process optimization and ease of construction, especially in terms of environmental protection and finishing effect.
[0087] Test Experiment Design:
[0088] Purpose of the experiment: To compare the performance of different concrete processes in terms of decorative effect, surface cleanliness, strength and durability.
[0089] Testing process:
[0090] Test sample preparation:
[0091] Make five concrete sample plates with different mix proportions and processes, with specifications of 300mm×300mm×50mm. Make 5 samples for each process, for a total of 25 samples.
[0092] The molding and curing time of each sample is 7 days, and it is guaranteed to be fully cured before testing.
[0093] Test items:
[0094] Decorative effect test: Evaluated by the clarity and natural appearance of the surface sand and stone contours.
[0095] Cleanability Test: Simulates daily dust accumulation to test the cleanability of the surface.
[0096] Concrete Strength Test: The overall strength of concrete is assessed through compressive strength testing.
[0097] Durability Testing: Testing the durability and crack resistance of concrete by simulating pedestrian loads and weathering on the trail.
[0098] Economic evaluation: Compare construction costs, maintenance costs and other factors to conduct economic benefit analysis.
[0099] Test experiment process
[0100] 1.Decoration effect testing process
[0101] Evaluation method: The sand and gravel contours formed on the surface of each sample are photographed with a high-precision camera, and image analysis software is used to evaluate the surface texture clarity. The area ratio of naturally appearing sand and gravel and the smoothness of the contour are recorded.
[0102] Data indicators:
[0103] Natural appearance rate of sand and gravel (%)
[0104] Sand and gravel contour clarity score (1-10)
[0105] 2. Cleaning performance test process
[0106] Evaluation method: Sprinkle dust on the concrete surface to simulate daily dust accumulation. Then clean it with a high-pressure water gun and record the amount of dust remaining on each sample after cleaning. Test the amount of dust remaining on the surface and the cleaning time.
[0107] Data indicators:
[0108] Cleaning residual dust (g / m 2 )
[0109] Cleaning time (seconds)
[0110] 3. Concrete strength test process
[0111] Evaluation method: Use a standard compressive strength testing machine to test the compressive strength of the sample, record the compressive strength value of each process, and load according to the standard process until it is destroyed.
[0112] Data indicators:
[0113] Compressive strength(MPa)
[0114] 4. Durability test process
[0115] Evaluation method: simulate sidewalk loads and natural weathering. After each sample is subjected to 1,000 simulated load impacts, the length and depth of the surface cracks are measured, and the damage to the sample is recorded.
[0116] Data indicators:
[0117] Crack length(mm)
[0118] Crack depth(mm)
[0119] Degree of damage to the sample (1-5 rating)
[0120] 5. Economic evaluation process
[0121] Evaluation method: Compare the material cost, construction hours, and subsequent maintenance requirements of each process, calculate the economic benefits, and give the comprehensive cost per square meter of sidewalk pavement for each process.
[0122] Data indicators:
[0123] Construction cost per square meter (yuan / m 2 )
[0124] Maintenance cost (yuan / year / m 2 )
[0125] Experimental data and test results
[0126] 1.Decoration effect test results:
[0127]
[0128]
[0129] 2. Cleaning performance test results:
[0130] Example <![CDATA[Clean residual dust amount (g / m 2 )]]> Cleaning time (seconds) Embodiment 1 0.2 15 Embodiment 2 0.8 35 Embodiment 3 1.0 40 Embodiment 4 0.5 25 Embodiment 5 1.2 50
[0131] 3.Concrete strength test results:
[0132] Example Compressive strength(MPa) Embodiment 1 60 Embodiment 2 45 Embodiment 3 50 Embodiment 4 48 Embodiment 5 42
[0133] 4. Durability test results:
[0134]
[0135]
[0136] 5. Results of economic evaluation:
[0137] Example <![CDATA[Construction cost per square meter (yuan / m 2 )]]> <![CDATA[Annual maintenance cost (yuan / year / m 2 )]]> Embodiment 1 250 5 Embodiment 2 300 20 Embodiment 3 280 15 Embodiment 4 260 10 Embodiment 5 320 25
[0138] Results Analysis and Summary
[0139] Decorative effect: Example 1 showed a very high natural sand and stone appearance rate (95%), and the highest outline clarity score (9 points), no secondary treatment was required, and it fully met the requirements of high efficiency and environmental protection. The sand and stone appearance rate and clarity of other examples were lower, especially the acid erosion method of Example 5 had the worst effect.
[0140] Cleaning performance: The surface of Example 1 is easy to clean, and the residual dust is the lowest (0.2g / m 2 ), the cleaning time is the shortest (15 seconds), showing the advantages of natural transition of surface shape and easy cleaning. Example 5 Due to the acid washing, the surface is irregular, the cleaning residue is the largest and the cleaning time is the longest.
[0141] Concrete strength: Example 1 has the highest compressive strength (60MPa), and its dense structure ensures the wear resistance and original appearance of the surface, meeting the requirement of not needing to apply transparent protective coating. In other examples, the compressive strength of traditional processes is generally low, especially in Examples 2 and 5, which have low strength and are easily damaged.
[0142] Durability: Example 1 has the best durability, with the smallest crack length and depth, and the lowest surface damage. The traditional process (such as Examples 2 and 5) has a loose structure, more and deeper cracks, and more serious damage.
[0143] Economical: The construction cost of Example 1 is moderate (250 yuan / m 2 ), but the maintenance cost is the lowest (5 yuan / year / m 2 ), showing the best long-term economic benefits. The fifth embodiment has the highest cost and high maintenance costs, showing the worst economic performance.
[0144] Summarize:
[0145] It can be clearly seen from the test data that the high-quality decorative concrete with sand and gravel (Example 1) of the present invention is superior to other traditional processes in terms of decorative effect, cleaning performance, strength and durability, especially the construction cost is moderate and the maintenance cost is extremely low. Compared with other traditional processes, the present invention has obvious technical advantages and economic benefits, and is suitable for promotion and application in high-demand concrete pavement scenes such as sidewalks.
[0146] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. High-quality concrete with sand and gravel decoration, characterized by: It includes the following components: 400 to 500 parts of cement, 20 to 25 parts of reinforcing agent, 0.4 to 0.5 parts of defoaming powder, 12 to 16 parts of water reducing agent, 115 to 147 parts of water, 117 to 147 parts of extra fine sand, 591 to 739 parts of medium fine sand, 443 to 560 parts of coarse sand, 443 to 560 parts of gravel, and 0.3 to 0.5 parts of admixture.
2. The high-quality decorative concrete with sand and gravel properties according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer, which is specifically copolymerized from polyether monomer, acrylic acid, ammonium persulfate, thioglycolic acid, maleic anhydride, phosphate ester and the like.
3. The high-quality decorative concrete with sand and gravel properties according to claim 1, characterized in that: The additive is a shrinkage reducing agent, which is specifically composed of polypropylene glycol, ethylene oxide methanol additives, ethylene oxide propylene oxide block polymers, ethylene oxide propylene oxide random polymers, ethylene oxide cycloalkyl additives, ethylene oxide methyl additives, ethylene oxide phenyl additives, ethylene oxide propylene oxide block polymer methyl phenyl additives, ethylene oxide methanol added at both ends, and ethylene oxide dimethylamine additives.
4. The high-quality decorative concrete with sand and gravel properties according to claim 1, characterized in that: The diameter of the medium-fine sand ranges from 0.3mm to 0.8mm, the diameter of the extra-fine sand ranges from 0.075mm to 0.3mm, the diameter of the coarse sand ranges from 0.8mm to 5.1mm, and the diameter of the stone ranges from 3mm to 10mm.
5. A construction method for high-quality decorative concrete with sand and gravel properties, according to the high-quality decorative concrete with sand and gravel properties described in any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Material preparation: During the material preparation stage, the following materials must be accurately weighed in proportion: cement, reinforcing agent, defoaming powder, water reducing agent, water, sand, gravel and admixtures. After all materials are prepared, they should be placed in the designated area in order to ensure that the proportions are correct before construction. S2. Mixing cement slurry: First, corresponding amounts of cement and reinforcing agent are mixed as predetermined, and added into a mixer at a suitable temperature, then defoaming powder and admixture are added, and finally, water and water reducing agent are premixed to obtain a composite solution A, and then the composite solution A is slowly poured into the mixer and stirred to obtain a uniform cement slurry with no segregation and good fluidity; S3, mixing cement mortar: after the mixing in step S2 is completed, the temperature of the mixer is maintained, and then ultra-fine sand is first added and then medium-fine sand is added to make cement mortar; S4, mixing to concrete: maintaining the mixer speed in step S3, adding coarse sand and gravel to the cement mortar and mixing to form slightly unsaturated concrete; S5. Concrete pouring: Pour the mixed concrete evenly into the mold, use high-frequency vibrating equipment to compact the concrete, and quickly level it after compaction to ensure that the concrete surface is aligned with the predetermined elevation; S6. Curing concrete: After pouring the concrete, cover it with wet cotton cloth for moisturizing. The wet cotton cloth needs to be covered overhead, and then covered with a layer of plastic film to keep it airtight and the wet cotton cloth moist. Curing takes 7 to 14 days.
6. The method for constructing high-quality concrete with sandstone decoration according to claim 5, characterized in that: In the step S2, the mixed water and water reducing agent are added into a mixer, and the speed of stirring is 30 r / min to 50 r / min, and the stirring time is 3 min to 5 min.
7. The method for constructing high-quality concrete with sandstone decoration according to claim 5, characterized in that: In the step S3, when adding the ultra-fine sand and fine sand, the rotation speed of the mixer is 40 r / min to 60 r / min, and the stirring time is 5 min to 8 min.
8. The method for constructing high-quality concrete with sandstone decoration according to claim 5, characterized in that: In the step S5, the vibration frequency of the high-frequency vibration equipment is 3000 times / min to 5000 times / min, and each position needs to be vibrated for 5S to 10S.
9. The method for constructing high-quality concrete with sandstone decoration according to claim 5, characterized in that: In the step S6, the wet cotton cloth must not directly contact the concrete surface and must be replenished with water in time to keep it moist. The curing temperature must be maintained above 8°C.